Digital strategy for improving resilience of micro, small, and medium enterprises - Issa Dyah Utami; Trisita Novianti; Fachrizal Setiawan (Jurnal Sistem dan Manajemen Industri, 2023)
The COVID-19 pandemic impacted several small and medium-sized enterprises (SMEs) in Indonesia. The viability of some SMEs' business operations was disturbed, especially those who create non-essential goods like carving. The sales have decreased by up to sixty per cent, causing reduced levels of income and the termination of numerous workers. SMEs in Indonesia are highly considered because businesses are one of the country's most significant economic contributors. This research proposes a strategy for SMEs to improve the resilience of business operations of the SMEs. The K-means method was used to investigate three groups of SMEs: micro, small, and medium. Changes in the SME class before and after the pandemic are investigated through changes in the values of the variables in the SME profile. Then the SWOT method is used to identify internal and external factors with the highest weight, which can be used as a basis for developing strategies to increase the resilience of SMEs. Furthermore, the TOPSIS method determines the best plan for dealing with the new digital era. The result shows that the W-T strategy to utilize social media can be prioritized based on the criteria that significantly impact SMEs' product sales and business resilience.